Are Patients With Inflammatory Bowel Disease at an Increased Risk of Developing SARS-CoV-2 than Patients Without Inflammatory Bowel Disease? Results From a Nationwide Veterans' Affairs Cohort Study. (19th April 2021) - Khan, Nabeel; Patel, Dhruvan; Xie, Dawei; Pernes, Tyler; Lewis, James; Yang, Yu-Xiao
Abstract : INTRODUCTION: The clinic course of SARS-CoV-2 among patients with inflammatory bowel disease (IBD) has been extensively studied. However, there is a paucity of data on whether patients with IBD have an increased risk of developing SARS-CoV-2 with compared with patients without IBD. METHODS: We conducted a nationwide retrospective cohort study in the US Veterans' Affairs healthcare system from January 1, 2020, to June 30, 2020. We matched each patient with IBD with 2 patients without IBD on age, sex, race, location, and comorbidities. The outcome of interest was development of SARS-CoV-2. RESULTS: Among 38, 378 patients with IBD and 67, 433 patients without IBD, 87 (0.23%) and 132 (0.20%) patients developed incident SARS-CoV-2 infection, respectively ( P = 0.29). DISCUSSION: Patients with IBD are not at a significantly increased risk of developing SARS-CoV-2 infection when compared with patients without IBD.